The Importance of Macrophages, T-Lymphocytes and Passive Transfer of Antibody in the Protection of Mice against Shigella Dysenteriae Type 1. - Koleosho, Tinuola (Obafemi Awolowo University, 2014)
The contribution of T-lymphocytes, macrophages and antibodies to protection against Shigella dysenteriae type 1 during the course of infection in mice was analysed following intraperitoneal injection of the organism into mice.